1977
DOI: 10.1139/f77-231
|View full text |Cite
|
Sign up to set email alerts
|

Percids of Lake Constance, a Lake Undergoing Eutrophication

Abstract: A review of literature suggested that yield of Eurasian perch, Perca fluviatilis, in Lake Constance was greatest with moderate eutrophication. During eutrophication (1950–76), changes also took place in food, growth, distribution, and diseases of perch. Differences in perch between Lake Constance and other German or Alpine lakes of various degrees of eutrophy were found with respect to growth, yield, the relation of growth to yield, food, and the relation of food to growth. Similarities were apparent for perch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 0 publications
3
48
0
2
Order By: Relevance
“…Literature on species-area relationships indicates larger riverine systems often support higher diversity (Hugueny, 1989); consequently, the observed changes in parasite diversity may be positively influenced by increased habitat complexity and connectivity found in larger systems. However, previous research has demonstrated similar changes in parasite communities in relation to habitat quality as observed here (Hartmann and Nümann, 1977;MacKenzie, 1999;Zargar et al, 2012), and nutrient loading may dampen the speciesarea effect (Brönmark et al, 1984), providing further support for parasites as effective indicators of environmental characteristics. Truly disentangling the causal mechanisms regarding changes in parasite diversity such as what is observed here would require large-scale, systematic research program incorporating laboratory and field trials.…”
Section: Discussionsupporting
confidence: 79%
“…Literature on species-area relationships indicates larger riverine systems often support higher diversity (Hugueny, 1989); consequently, the observed changes in parasite diversity may be positively influenced by increased habitat complexity and connectivity found in larger systems. However, previous research has demonstrated similar changes in parasite communities in relation to habitat quality as observed here (Hartmann and Nümann, 1977;MacKenzie, 1999;Zargar et al, 2012), and nutrient loading may dampen the speciesarea effect (Brönmark et al, 1984), providing further support for parasites as effective indicators of environmental characteristics. Truly disentangling the causal mechanisms regarding changes in parasite diversity such as what is observed here would require large-scale, systematic research program incorporating laboratory and field trials.…”
Section: Discussionsupporting
confidence: 79%
“…Gillnetting showed that the vertical distribution varies with season. the depth of maximum catch increasing from 6 to 10 m in summer to more than 40 m in winter (Hartrnann & Niimann, 1977). Except for this general habitat shift.…”
Section: During Eutrophication Adult Perch Perm Fiuviatilis L Shiftementioning
confidence: 85%
“…Human activity has increased the number of highly productive, and therefore highly turbid, lakes significantly (Edmondson 1969). Concurrently with this development, changes in the structure of temperate lake fish communities were observed (Colby et al 1972;Hartmann and Nümann 1977). European lake fish communities dominated by salmonids and coregonids were replaced by percids, and those dominated by percids were replaced by cyprinids.…”
Section: Introductionmentioning
confidence: 96%